RET-HE DALAM DIAGNOSIS SEBAGAI TOLOK UKUR DALAM MENDETEKSI KEKURANGAN ZAT BESI DI IBU HAMIL (Ret-He in Diagnostic Parameter to Detecting Iron Deficiency in Pregnant Women) - Imee Surbakti; Adi Koesoema Aman; Makmur Sitepu (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Varieties of the laboratory test can be applied in the detecting of iron status. These test are divided into conventional hematologicindex and biochemical iron serum. With the development of an hematological analyzer, new parameter has been found to monitor theiron status with reticulocytes hemoglobin analysis (Ret-He). To know the diagnostic accuracy of Ret-He and to conclude whether Ret-Hecan be used as a parameter to detect iron deficiency in pregnant women by obtaining certain information. This study used analyticalcross sectional was conducted at Haji Adam Malik Hospital Medan, in March−June 2013. The Applying samples consisted of 64 thirdtrimester pregnant women which divided into two (2) groups: the noniron deficiency group using 28 subjects and in the iron deficiency36 subjects. In this study, the researchers found AUC for Ret-He about 77.7% with the best cut off value of <31.4 pg. Using the cut offvalue the researchers obtained the sensitivity about 61.1%, specificity 75.0%, Positive Predictive Value (PPV) 75.8%, Negative PredictiveValue (NPV) 60.0%, Likehood Ratio (LR) (+) 2.44 and LR (–) 0.51%. Based on this study, can be concluded, that the diagnostic accuracyRet-He is a good parameter to detect iron deficiency in the pregnant women.